2014
DOI: 10.1186/1471-2474-15-286
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic manipulative treatment for nonspecific low back pain: a systematic review and meta-analysis

Abstract: BackgroundNonspecific back pain is common, disabling, and costly. Therefore, we assessed effectiveness of osteopathic manipulative treatment (OMT) in the management of nonspecific low back pain (LBP) regarding pain and functional status.MethodsA systematic literature search unrestricted by language was performed in October 2013 in electronic and ongoing trials databases. Searches of reference lists and personal communications identified additional studies. Only randomized clinical trials were included; specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 54 publications
(110 reference statements)
5
89
0
22
Order By: Relevance
“…125–133 Conclusions from these systematic reviews for practitioner approaches (acupuncture, chiropractic, massage therapy) 125–131 and dietary supplements 132 were generally consistent with our findings. For instance, in a comprehensive reviews of both pharmacological and non-pharmacological approaches to manage back pain, Chou et al (20016) 125 found that acupuncture and yoga appear to be effective for improving pain and/or function in back pain.…”
Section: Safetysupporting
confidence: 84%
See 1 more Smart Citation
“…125–133 Conclusions from these systematic reviews for practitioner approaches (acupuncture, chiropractic, massage therapy) 125–131 and dietary supplements 132 were generally consistent with our findings. For instance, in a comprehensive reviews of both pharmacological and non-pharmacological approaches to manage back pain, Chou et al (20016) 125 found that acupuncture and yoga appear to be effective for improving pain and/or function in back pain.…”
Section: Safetysupporting
confidence: 84%
“…The authors of the systematic reviews concluded that yoga appears to be a viable option for relieving pain and discomfort associated with arthritis, but that larger, better designed trials were needed. A recent systematic review 131 that included international trials found that “clinically relevant effects of OMT were found for reducing pain and improving functional status” for those with back pain. Although this is a stronger conclusion than we reached, the authors’ identified deficiencies in trial methodology and called for larger, better quality RCT’s to provide firm conclusions.…”
Section: Safetymentioning
confidence: 99%
“…Some of these reviews further specified SMT as cervical, thoracic or lumbar SMT (21 reviews [46, 47, 49, 54, 57, 65, 91, 96, 103, 105, 114, 115, 119, 121, 123, 125–127, 134, 136, 150]). Other reviews did not further specify than ‘manipulation’ (10 reviews [36, 66, 70–73, 79, 93, 101, 107]), ‘osteopathic manipulative treatment/therapy’ (8 reviews [38, 52, 56, 64, 81, 82, 116, 139]), and ‘chiropractic care/interventions’ (5 reviews [67, 98–100, 137]).…”
Section: Resultsmentioning
confidence: 99%
“…Some limitations of our study are attributable to the fact that CMT entails contact with patients when treating, rendering it impossible to blind patients due to its method of treatment. Potential bias is a possible liability in this study design, but is difficult to control due to unblinding [3,48]. Experts considered sham control in meetings, but as CMT would generally be provided for an average of 15 min per patient, it was concluded that a sham-controlled trial would be unrealistic in Korean clinical settings.…”
Section: Discussionmentioning
confidence: 99%